The Role of the Central Nervous System Microenvironment in Pediatric Acute Lymphoblastic Leukemia - Gossai, Nathan P.; Gordon, Peter M. (Frontiers in Pediatrics, 2017)
Acute lymphoblastic leukemia (ALL) is the most common cancer in children. While survival rates for ALL have improved, central nervous system (CNS) relapse remains a significant cause of treatment failure and treatment-related morbidity. Accordingly, there is a need to identify more efficacious and less toxic CNS-directed leukemia therapies. Extensive research has demonstrated a critical role of the bone marrow microenvironment in leukemia development, maintenance, and chemo-resistance. Moreover, therapies to disrupt mechanisms of bone marrow microenvironment mediated leukemia survival and chemo-resistance represent new, promising approaches to cancer therapy. However, in direct contrast to the extensive knowledge of the bone marrow microenvironment, the unique attributes of the CNS microenvironment that serve to make it a leukemia reservoir are not yet elucidated. Recent work has begun to define both the mechanisms by which leukemia cells migrate into the CNS and how components of the CNS influence leukemia biology to enhance survival, chemo-resistance, and ultimately relapse. In addition to providing new insight into CNS relapse and leukemia biology, this area of investigation will potentially identify targetable mechanisms of leukemia chemo-resistance and self-renewal unique to the CNS environment that will enhance both the durability and quality of the cure for ALL patients.